Juridical Analysis Of Technology-Based Services To Support Increased Investment In The Free Trade Area And Free Port Of Batam (Research Study At The Batam Concession Agency) - Jerry Satriawan; Fadlan Fadlan; Lagat Parroha Patar Siadari; Erniyanti Erniyanti; Soerya Respationo (FKIP, Universitas Palangka Raya, 2023)
Technological developments to date have had a rapid impact on all aspects of life, including economic aspects and aspects of government administration; many things have arisen and have had positive impacts, such as ease of access to information and simplification of services by the government. So that technology-based services can be prepared and implemented based on a policy that cannot be separated from the legal theory that binds it. In order to support ease of investment services, the Government has initiated an Online Single Submission (OSS) system since October 2017 as an implementation of Presidential Regulation Number 91 of 2017 concerning the Acceleration of Business Implementation and has conducted concept trials in three locations, namely: Purwakarta, Batam, and Palu. The design of this Information Technology-based system is basically by interconnecting and integrating the existing licensing service system at BKPM/Central PTSP (SPIPISE), a regional PTSP that uses the Ministry of Communication and Information's SiCantik system. In practice, the licensing implemented uses a one-door system, which makes it quicker for investors to process port permits. In this case, BP Batam provides services in the form of Indonesia Batam Online Single Submission or IBOSS. Licensing that previously used manual or conventional methods has switched to an electronic system connected directly to the national system. Port permits are now also handled directly by the BP Batam One-Stop Integrated Services (PTSP) Directorate, which impacts the speedy completion of port permit processing. However, in implementing technology-based services, it is essential to pay attention to regulatory or legal aspects so that implementation remains safe and does not cause material or non-material losses. To safeguard data, the application guarantees that the data recorded by Business Actors is only for Business Licensing services. However, even though there are guarantees or clauses, comprehensive research must still be carried out regarding technology-based services in order to support increased investment, considering that data security is an essential thing in running services.